2021
DOI: 10.1016/j.brs.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold repetitive transcranial magnetic stimulation drives structural synaptic plasticity in the young and aged motor cortex

Abstract: Background: Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive tool commonly used to drive neural plasticity in the young adult and aged brain. Recent data from mouse models have shown that even at subthreshold intensities (0.12 T), rTMS can drive neuronal and glial plasticity in the motor cortex. However, the physiological mechanisms underlying subthreshold rTMS induced plasticity and whether these are altered with normal ageing are unclear. Objective: To assess the effect of subthreshold r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Studies with humans have shown that iTBS drives acute changes to motor behaviour and neuronal excitability. 60 A possible mechanism has been reported by an animal study showing that iTBS can promote neural structural remodelling and functional recovery by enhancing neurogenesis and migration via the miR-551b-5p/BDNF/TrkB pathway. 61 The first study of cerebellar vermis stimulation was reported in 1995, which investigated its effects on saccade metrics in a man via TMS.…”
Section: Discussionmentioning
confidence: 98%
“…Studies with humans have shown that iTBS drives acute changes to motor behaviour and neuronal excitability. 60 A possible mechanism has been reported by an animal study showing that iTBS can promote neural structural remodelling and functional recovery by enhancing neurogenesis and migration via the miR-551b-5p/BDNF/TrkB pathway. 61 The first study of cerebellar vermis stimulation was reported in 1995, which investigated its effects on saccade metrics in a man via TMS.…”
Section: Discussionmentioning
confidence: 98%
“…The rTMS-induced changes to cortical physiology have been suggested to resemble those occurring during the critical or sensitive period of development [ 46 ] and may increase the capacity for plasticity in the mature brain [ 47 , 48 , 49 ]. For example, rTMS has been shown to increase the expression of brain-derived neurotrophic factor (BDNF) [ 21 , 22 , 50 , 51 , 52 ], disinhibit cortical circuits [ 53 , 54 , 55 , 56 ], and alter dendritic spine density in motor cortex [ 57 ]. Thus, the outcomes of rTMS-based therapies may modify and facilitate the removal of barriers to adult plasticity to create a more adaptive environment, in which endogenous brain activity can drive relevant and beneficial functional changes.…”
Section: Discussionmentioning
confidence: 99%
“…Cranial windows were implanted in nine 12-week-old NG2DsRed x CX3CR1 +/GFP mice as described previously 60 , with modification; windows were implanted without a titanium bar glued opposite the window and were placed over the primary somatosensory cortex, specifically over the upper, lower and trunk domain areas. In vivo two-photon laser scanning microscopy (2PLSM) was performed using the same microscope and software as previously described 60 and was performed during the mouse light cycle. To image blood vessels, mice were intravenously (via the tail vein) administered 2% w/v FITC-dextran in saline (70,000 Da; Sigma-Aldrich, USA) 10 minutes prior to imaging.…”
Section: Cranial Widow Implantation and In Vivo Two-photon Imagingmentioning
confidence: 99%
“…To image blood vessels, mice were intravenously (via the tail vein) administered 2% w/v FITC-dextran in saline (70,000 Da; Sigma-Aldrich, USA) 10 minutes prior to imaging. Mice were anesthetised with isoflurane in a chamber, then transferred to a stereotaxic frame, where isoflurane was delivered through a facemask at 2-3% concentration in oxygen, as required, to maintain anaesthesia 60 . An EC Plan-Neofluar 20X/0.1 water immersion objective (Nikon, USA), illuminated by white light, was used to identify large blood vessels in the somatosensory cortex (layers II/III) that were subsequently used as landmarks for regions of interest (ROIs).…”
Section: Cranial Widow Implantation and In Vivo Two-photon Imagingmentioning
confidence: 99%